2022
DOI: 10.1101/2022.09.20.22280150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge Mapping of Nigeria’s Scientific Contribution to Antimicrobial Resistance Research: A visualized investigation using VOS viewer and Cite Space

Abstract: Objective: A comprehensive overview of the research output, including conceptual and temporal trends, is required to address the growing AMR burden in Nigeria, which was previously lacking. This study uses bibliometric analysis to show this. Methods: Data from a query of AMR articles in the Dimensions database (PubMed included) were subjected to bibliometric analysis (1972 to 2022). Bibliometric indicators, topic networks were established and topic trends were analyzed by frequency, relevance scores, and tren… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…A comprehensive overview of the research output in Nigeria, including conceptual and temporal trends, is crucial to address the country's growing Antimicrobial Resistance (AMR) burden. A bibliometric analysis conducted by provided a detailed insight into the AMR research output in Nigeria from 1972 to 2022 (Adeiza et al, 2022). The study revealed that only 0.2% of the papers on AMR published worldwide were written by authors or institutions from Nigeria.…”
Section: Efficacy Of Laboratory Science Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive overview of the research output in Nigeria, including conceptual and temporal trends, is crucial to address the country's growing Antimicrobial Resistance (AMR) burden. A bibliometric analysis conducted by provided a detailed insight into the AMR research output in Nigeria from 1972 to 2022 (Adeiza et al, 2022). The study revealed that only 0.2% of the papers on AMR published worldwide were written by authors or institutions from Nigeria.…”
Section: Efficacy Of Laboratory Science Contributionsmentioning
confidence: 99%
“…The study highlighted the areas of focus for Nigerian researchers, including antimicrobial stewardship, clinical and laboratory practices on AMR, public health implications, traditional and molecular methods, and phytomedicine and drug discovery. The study concluded that there is a need for increased research capacity to address the burden of AMR in Nigeria and emphasized the importance of innovation for the future of antibiotics (Adeiza et al, 2022).…”
Section: Efficacy Of Laboratory Science Contributionsmentioning
confidence: 99%